Recycling For Dummies - Winkler, Sarah, author (Indianapolis : John Wiley and Sons, 2023)
"Recycling is a simple action we can take that has an immediate positive effect. It keeps waste out of landfills, conserves natural resources, prevents pollution, and saves energy. Who wouldn't want to do this? But recycling isn't always straightforward. With so many different rules, it can be tough to work out the right thing to do. If you're worried that you're not recycling properly, or wondering whether you could be recycling more, this is the book for you. Recycling For Dummies cuts through the confusion around what you can and can't recycle. This easy-to-follow manual breaks down recycling codes, symbols, and rules in a straightforward way that anyone can understand and apply. You'll gain insight into the recycling process (where does that stuff go, anyway?) and learn tons of tips on reusing items in your daily life to cut down on waste. It also guides you on how to make smarter choices as a consumer to help preserve the planet for generations to come."--Publisher marketing